Pengaruh Penggunaan Model Inquiry Learning Terhadap Keterampilan Menulis Teks Eksposisi Siswa Kelas VIII SMP Negeri 3 Marioriwawo Kabupaten Soppeng - Qhatimah, Husnul; Sultan, Sultan; Fitri, Sakinah (Nuances of Indonesian Language, 2025)
This research aims to (1) describe the expository text writing skills of Class VIII students at SMP Negeri 3 Marioriwawo before using the inquiry learning model; (2) describe the expository text writing skills of Class VIII students at SMP Negeri 3 Marioriwawo after using the inquiry learning model; (3) prove the effect of using the inquiry learning model on exposition text writing skills for Class VIII SMP Negeri 3 Marioriwawo. The type of research used is quantitative research using the Pre-Experimental method. The data collection technique in this research is a task that is divided into Pretest and Posttest. The population of this research was all students in class VIII of SMP Negeri 3 Marioriwawo which consisted of 3 classes with a total of 90 students and the sample was taken using the Simple Random Sampling Technique, so the researcher determined the research sample to be 73 students using the Krejcie and Morgan tables. The data analysis used in this research is descriptive statistical analysis and inferential statistical analysis. The learning outcomes of expository text writing skills before using the inquiry learning model for Class VIII students at SMP Negeri 3 Marioriwawo are in the less skilled category with an average score of 55. The learning outcomes for expository text writing skills after using the inquiry learning model for Class VIII students at SMP Negeri 3 Marioriwawo, is in the skilled category with an average score of 81. Based on the Paired Sample Test in the t test above, it is known that the significant value = 0.000 from 73 students. The value is 0.000< 0.05, so it can be stated that Ho is rejected and H1 is accepted, thus it can be concluded that the use of the Inquiry Learning model for writing expository texts for Class VIII students at SMP Negeri 3 Marioriwawo has a significant effect.